The Immunomodulatory Properties of Mesenchymal Stem Cells Play a Critical Role in Inducing Immune Tolerance after Liver Transplantation - Shao-wei Li; Yue Cai; Xin-li Mao; Sai-qin He; Ya-hong Chen; Ling-ling Yan; Jing-jing Zhou; Ya-qi Song; Li-ping Ye; Xian-bin Zhou (Hindawi Limited, 2021)
Although liver transplantation is considered to be the best choice for patients with end-stage liver diseases, postoperative immune rejection still cannot be overlooked. Patients with liver transplantation have to take immunosuppressive drugs for a long time or even their entire lives, in which heavy economic burden and side effects caused by the drugs have become the major impediment for liver transplantation. There is a growing body of evidences indicating that mesenchymal stem cell (MSC) transplantation, a promising tool in regenerative medicine, can be used as an effective way to induce immune tolerance after liver transplantation based on their huge expansion potential and unique immunomodulatory properties. MSCs have been reported to inhibit innate immunity and adaptive immunity to induce a tolerogenic microenvironment. In in vitro studies, transplanted MSCs show plasticity in immune regulation by altering their viability, migration, differentiation, and secretion in the interactions with the surrounding host microenvironment. In this review, we aim to provide an overview of the current understanding of immunomodulatory properties of MSCs in liver transplantation, to elucidate the potential mechanisms behind MSCs regulating immune response, especially in vivo and the influence of the microenvironment, and ultimately to discuss the feasible strategies to improve the clinical prognosis of liver transplantation. Only after exhaustive understanding of potential mechanisms of the MSC immunomodulation can we improve the safety and effectiveness of MSC treatment and achieve better therapeutic effects.